Module Over a Division Ring - Blyth Theorem 1.1, Part 4

In summary, Peter proves that if ##R## is a division ring and ##\lambda x = 0_M## with ##\lambda \neq 0_R## then we have that ##x = 0_M##. However, he still wonders why this logic bothers him.
  • #1
Math Amateur
Gold Member
MHB
3,998
48
I am reading T. S. Blyth's book "Module Theory: An Approach to Linear Algebra" ... ... and am currently focussed on Chapter 1: Modules, Vector Spaces and Algebras ... ...

I need help with an aspect of Theorem 1.1 part 4 ...

Theorem 1.1 in Blyth reads as follows:
?temp_hash=130091d5b5e518dfcff28c7ba4b6c3d1.png


In the above text, in part 4 of the Theorem we read:" ... ... when ##R## is a division ring

(4) ##\lambda x = 0_M## implies ##\lambda = 0_R## or ##x = 0_M## ... ... "Blyth proves that if ##R## is a division ring and ##\lambda x = 0_M## with ##\lambda \neq 0_R## then we have that ##x = 0_M## ... ...But ... ... Blyth does not show that if ##R## is a division ring and ##\lambda x = 0_M## with ##x \neq 0_M## then we have that ##\lambda = 0_R## ... ...Can someone please help me to prove this ...

Peter
 

Attachments

  • Blyth - Theorem 1.1.png
    Blyth - Theorem 1.1.png
    53.4 KB · Views: 1,248
Physics news on Phys.org
  • #3
micromass said:
Contrapositive.

Sorry Micromass ... I do not follow you ...

Can you explain what you mean more explicitly ... ?

My apologies for not following you ...

Peter
 
  • #5
  • #6
Math Amateur said:
Hi Micromass ... I understand the meaning of "contrapositive" ... but fail to see exactly how it applies to the problem that I posed ...

Can you be more explicit in what you mean regarding the specific problem ...

Peter
 
  • #7
Come on, think a bit about it. You answered merely 6 minutes after me. I'm not here to spoonfeed you the answer.
 
  • #8
Proof of (4).
Case 1: ##\lambda = 0_R## ##\checkmark## by (2)
Case 2: ##\lambda \neq 0_R## - see Blyth's proof
 
  • Like
Likes Math Amateur
  • #9
fresh_42 said:
Proof of (4).
Case 1: ##\lambda = 0_R## ##\checkmark## by (2)
Case 2: ##\lambda \neq 0_R## - see Blyth's proof
Well ... thanks fresh_42 ... that is an easy resolution to the issue ...

BUT ... still reflecting and wondering about Case 1 ...

... indeed ... does ##( 0_R x = 0_M )## ...

... imply (or mean) that ...

##( \lambda x = 0_M \text{ and } x \neq 0_M \Longrightarrow \lambda 0_R )##

is true ...But why exactly ... ?(Not quite sure why this logic bothers me ...)

Peter
 
Last edited:
  • #10
Thanks for th
Math Amateur said:
Well ... thanks fresh_42 ... that is an easy resolution to the issue ...

BUT ... still reflecting and wondering about Case 1 ...

... indeed ... does ##( 0_R x = 0_M )## ...

... imply (or mean) that ...

##( \lambda x = 0_M \text{ and } x \neq 0_M \Longrightarrow \lambda 0_R )##

is true ...But why exactly ... ?(Not quite sure why this logic bothers me ...)

Peter

micromass said:
Contrapositive.

micromass said:
Contrapositive.
Thanks for the hint, micromass ...

in (4) Blyth has shown the following:

##( \lambda x = 0_M \text{ and } \lambda \neq 0_R ) \longrightarrow (x = 0_M)## ... ... ... (1)

So ... contrapositive of (1) is as follows:

##\neg ( x = 0_M) \longrightarrow \neg ( \lambda x = 0_M \text{ and } \lambda \neq 0_R )##

But ... how do I progress from here ...

Can someone help further ...?

Peter
 
  • #11
We have ##\lambda x = 0_M## as a fact.
(2) is needed to show that ##\lambda = 0_R## is a solution at all.
Since there are only the two possibilities for ##\lambda## - either being zero or not - and the first solves the condition according to (2), it is sufficient to consider the other case, ##\lambda \neq 0_R##.

You may write the whole thing as:

##[\lambda x = 0_M] ##
##= \; (\lambda x = 0_M) \, ∧ \, \text{ (true) }##
##= \; (\lambda x = 0_M) \, ∧ \, [(\lambda = 0_R)\, ∨ \, (\lambda \neq 0_R)]##
##= \; [(\lambda x = 0_M) \, ∧ \, (\lambda = 0_R)] \, ∨ \, [(\lambda x = 0_M) \, ∧ \, (\lambda \neq 0_R)]##

→ (now I use (2), i.e. if ##\lambda = 0_R## is true then ##\lambda x = 0_M## is also true)

##= \; (\lambda = 0_R)\, ∨ \, [(\lambda x = 0_M) \, ∧ \, (\lambda \neq 0_R)]##

Therefore if ##(\lambda = 0_R) = \text{ (true) }## we are done and we may ask when ##[(\lambda x = 0_M) \, ∧ \, (\lambda \neq 0_R)]## will be true without ##(\lambda = 0_R)## being true, i.e. ##(\lambda \neq 0_R)##. Now Blyth has shown

$$[(\lambda x = 0_M) = \text{ (true) }] \,⇔\, [(\lambda = 0_R)=\text{ (true) }]\, ∨ \, [((\lambda x = 0_M) \, ∧ \, (\lambda \neq 0_R)) \,=\, \text{ (true) }]\, \overset{Blyth}⇒\, [(\lambda = 0_R)=\text{ (true) }]\, ∨ \, \; [(x=0_M) \,=\, \text{ (true) }]$$
 
Last edited:
  • Like
Likes Math Amateur
  • #12
Thanks for that fresh_42 ... most helpful ...

Much appreciate your assistance ...

Peter
 
Back
Top